Examining the effects of science curriculum and activities developed for gifted students in Turkey - Ayverdi, Leyla; Girgin, Derya; Satmaz, İsmail; Yalçınkaya Önder, Eylem (Journal of Interdisciplinary Studies in Education, 2024)
This study employed a mixed-methods design to investigate the impact of activities developed by the Ministry of National Education (MoNE) on the scientific creativity and scientist perceptions of gifted 5th-grade students. The research used a one-group pretest-posttest design with a sample of 22 students from a Science and Art Education Centre in a northwestern province of Türkiye. Quantitative data were collected using the "Scientific Creativity Test" and "Draw a Scientist Test", while qualitative data were gathered through an opinion form and a metaphor generation task. Results indicated that the activities significantly enhanced scientific creativity but did not alter scientist perceptions. Qualitative findings revealed that students developed more positive views of science and scientists, finding the activities both engaging and informative.